If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -22 = 4x + -3 Reorder the terms: -22 = -3 + 4x Solving -22 = -3 + 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. -22 + -4x = -3 + 4x + -4x Combine like terms: 4x + -4x = 0 -22 + -4x = -3 + 0 -22 + -4x = -3 Add '22' to each side of the equation. -22 + 22 + -4x = -3 + 22 Combine like terms: -22 + 22 = 0 0 + -4x = -3 + 22 -4x = -3 + 22 Combine like terms: -3 + 22 = 19 -4x = 19 Divide each side by '-4'. x = -4.75 Simplifying x = -4.75
| 3x-11=8x-12 | | 3(-x+2)=10 | | .6y+.4=6.4 | | 4y-4=-6(y-1) | | 126x^2-47x-385=0 | | -4(v+2)=3v-29 | | 3z+4x-5=0 | | .5(x-2.3)=1.8 | | 2+x-3+x=9+x | | x^4+x-50=0 | | 10(t-5)+4t=7(2t+3)-10 | | 3x+9=2(x+7) | | x+6*2=x-13 | | t+2t-19=0 | | -3(-x)+3x=24 | | 3(a-2)=10 | | 3k-8=-3k+10 | | 2y+2y-8+3y=9 | | 5x-5=4x+9 | | 0=6y+6 | | RT=2x+4 | | 3x+5x-5=11 | | 8-2p=p+3 | | (5x-2)(3x+2)=0 | | a-9a+18=0 | | 15=-3(m+5) | | x^4+3x^3-3x^2-11x-6=0 | | 3x+4x-9=19 | | 3x+5=0.2(15x+10) | | p=s+6 | | 0.25+0.10(x+85)=15.25 | | y=15x-30 |